Um novo território jurisdicional, uma nova dinâmica sociopolítica: o sertão do Piancó e os reflexos políticos da segunda metade do século XVIII no interior da Paraíba - Lacerda, Larissa Daniele Monteiro (2021)
The second half of the 18th century was one of the most intense periods in the history of the Portuguese kingdom and, especially, of Portuguese America, given the administrative, economic and political transformations arising from the Pombaline reforms. The creation of the Village of Pombal, in the hinterland of Piancó, in 1772, is only one of the reflexes of these changes in the captaincy of Paraíba. Its installation was significantly important, because, in addition to making viable the royal project of appropriation, control and organization of the territory, it made it possible for the Piancó hinterland to have its own chamber, an institution that joined the other existing authorities (military, legal and religious), since the end of the 17th century and the beginning of the 18th, and provided some kind of autonomy and bargaining power to the men of that hinterland. In this new context, political conflicts broke out at the internal and external levels, involving local and coastal authorities, which placed Piancó and the Village of Pombal in a prominent position in the political scenario of the captaincy, thus indicating possible changes in their local dynamics. And it is this dynamic that we investigate. The present work aims to analyze the changes that took place in the socio-political dynamics of the Piancó backlands in the second half of the 18th century, a period in which the creation and administrative organization of its new jurisdictional territory, the Village of Pombal. For this, in addition to the use of specialized bibliography (classical and academic), we rely on the analysis of official and manuscript sources, produced throughout the 18th century, both locally and externally. They are: royal orders, correspondence, population maps, council terms of the senate of the chamber of Pombal and notary sources.